Transition Metal Complexes Derived From 1,3-Dioxalane Groups and vic-Dioxime Ligands: Thermal, Magnetic and Spectral Studies - Duman, Sibel; Sekerci, Memet (Asian Journal of Chemistry, 2010)
A novel substituted vic-dioxime ligand containing the amino group, N,N'-[4,4'-ethane-1,2-diyl- bis(oxy)bis(4,1-phenylene)bis(N'-hydroxy)-2-(hydroxyimino)acetamidamide] (L1) has been prepared from 1,2-bis(p-aminophenoxy)ethane, anti-chloroglyoxime. This vic-dioxime ligand with Cu(II), Ni(II), Co(II) and Cd(II) complexes of 6,7-O-cyclopentylidine-1-amino-4-azaheptane (L2) have been reacted at 60-65 ºC temperature. The ligand1:metal:ligand2 ratio of these complexes have been found to be 1:2:2. The Cu(II), Ni(II), Co(II) and Cd(II) complexes of these ligands are proposed to be octahedral. The vic-dioxime (L1) with some transition metal complexes of amine (L2) have been characterized by elemental analyses, molar conductivity, magnetic susceptibility, IR, 1H NMR, UV-Vis spectra and TGA techniques.